Manajemen Pemasaran Perpustakaan Perguruan Tinggi - Novy Diana Fauzie (UGM, 2014)
Muhammadiyah University of Yogyakarta (UMY) always struggles to improve the quality of its alumni and direct its thorough educational process to be A Leading and Islamic University. Considering the aim, Library becomes a significant element to conduct researches and or scientific papers that can be used as references nationally and internationally, create academic atmosphere in growing open thoughts, critical-constructive, and innovative thoughts. UMY’s Library conducts some improvements and improve its service quality in order to be more well-known and useful for its academic community. This research aims at finding how the Library of UMY marketing management is and how SWOT analysis to library marketing mix in applying the appropriate strategies of library development. This research applies descriptive-qualitative method. The source of this research is Vice Chancellor I of UMY, Head of UMY’s Library, Library Staff, UMY’s librarian and 16 students. The data is collected through interviews, observations, and documents analysis. The data analysis is done by reducing data, displaying data, verifying, and making conclusion. This research results show that the Library of UMY has conducted a good management process. However, some problems are still found in marketing management. Marketing management of the Library of UMY covers Research STP Strategy, Marketing Mix, Implementation and Control. The early research done has reached a good SWOT analysis and creates a strategic strategy for 5 years (2012-2017). The Library of UMY conducts some efforts that are adjusted annually. STP Strategy learns about major librarian that is students, about their expectations, needs, and their image of the library. Marketing mix consists of Product, Price, Place, and Promotion. It becomes very crucial to master it especially about strength, weakness, chance, and challenge/threat. By analyzing SWOT 4 Ps, the recommended strategies for library development in the future can be applied. The Library Human Resources, both in quantity and quality, become its biggest threat in implementing the work plan. Controlling the work plan implementation becomes very important especially when it is done by many parties such as university, the head of the library, staff, and students. The library marketing management is better done by all libraries because the improvement will be useless when it is not marketed. Library service utilization and trust given by customers to the human resources of the library become a benchmark of the applied marketing success